NUCLEAR ENERGY AND TECHNOLOGY: Ecological-Sociological Impacts with Special Reference to Koodankulam, India - Celestine Soosai, Sahaya (Journal of Dharma, 2014)
The greenhouse effect has awakened the world to look for an alternative energy security, and 2011 Fukushima has threatened the world on the danger of the Nuclear Energy. In recent times, the developed countries concentrate on Renewable Energy Resources, while developing countries continue to invest in the nuclear plants and African countries have the desire to invest in Nuclear Energy. This research tackles the question of Nuclear Energy Security and the future of the Universe from philosophical and ecological perspectives. The study is based on the ecological and sociological impact of the Nuclear Project at Koodankulam in India.